Electron attachment and quantum coherence in molecular hydrogen. Issue 5 (January 2020) - Prabhudesai, Vaibhav S; Mason, Nigel J; Krishnakumar, E
Abstract: Single electron attachment to a molecule may invoke quantum coherence in different angular momentum transfer channels. This has been observed in the 14 eV dissociative electron attachment resonance in molecular hydrogen where a coherent superposition of two negative ion resonant states of opposite parity is created, with the s and p partial waves of the electron contributing to the attachment process. Interference between the two partial wave contributions leads to a forward – backward asymmetry in the angular distribution of the product negative ions. Since these two resonant states dissociate to the same n = 2 state of H and H −, this asymmetry is further modified due to interference between the two paths of the dissociating molecular negative ion along different potential energy curves. This interference manifests as a function of the electron energy as well as isotopic composition. This case is akin to the quantum interference observed in photodissociation by one-photon vs two-photon absorption.